A review: Polysaccharides targeting mitochondria to improve obesity - Chen, Yongchao; Gao, Rong; Fang, Jun; Ding, Sujuan (International journal of biological macromolecules, 2024)
Polysaccharides are one of the most important and widely used bioactive components of natural products, which can be used to treat metabolic diseases. Natural polysaccharides (NPs) have been the subject of much study and research in the field of treating obesity in recent years. Studies in the past have demonstrated that mitochondria are important for the initiation, progression, and management of obesity. Additionally, NPs have the ability to improve mitochondrial dysfunction via a variety of mechanisms. This review summarized the relationship between the structure of NPs and their anti-obesity activity, focusing on the anti-obesity effects of these compounds at the mitochondrial level. We discussed the association between the structure and anti-obesity action of NPs, including molecular weight, monosaccharide composition, glycosidic linkage, conformation and extraction methods. Furthermore, NPs can demonstrate a range of functions in adipose tissue, including but not limited to improving the mitochondrial oxidative respiratory chain, inhibiting oxidative stress, and maintaining mitochondrial mass homeostasis. The purpose of this work is to acquire a thorough understanding of the function that mitochondria play in the anti-obesity effects of NPs and to offer fresh insights for the investigation of how NPs prevent obesity and the creation of natural anti-obesity medications.